Teknik Assertive Training Melalui Konseling Kelompok Untuk Meningkatkan Interaksi Sosial Siswa - Sri Ratnasari; Andi Agustan Arifin (ILIN Institute, 2021)
The purpose of this study is to improve students' social interaction through group counseling with assertive training techniques at SMA Negeri 3 Morotai. The study method used quantitative research. The study used True Experimental Design in the form of Pretest-Posttest Control Group Design. The population in this study was 165 students in grade XI of SMA Negeri 3 Morotai and identified as having low social interaction as many as 44 students. Withdrawal of samples by probability sample method. The sample of 22 students with reference to the maximum number in group counseling generally consisted of about 4 to 12 people. Data collection techniques used in this research were questionnaires, observations, and student responses. Data analysis techniques used descriptive statistical techniques and inferential statistics. Hypothetical testing used non-parametric Wilcoxon Signed Ranks Test (Z) analysis of pretests and posttests. The results showed that the level of social interaction of students at SMA Negeri 3 Morotai, from the pre-test results of both the experimental and control groups was in low category. Based on the results of the analysis through the Wilcoxon Signed Ranks Test (Z), there was a significant difference in average value after being treated in the experimental group, this was confirmed by the gain score in the experimental group of 64,727. In the control group there was no significant difference in average value, this was confirmed by the gain score in the control group of 13.63.